Hak Dan Kewajiban Para Pihak Dalam Menjaga Rahasia Dagang Franchise - Alkautsar Raga Trenggono; Budi Ispriyarso (Notarius, 2022)
AbstractThere are many franchise businesses, one of which was researched in this writing is the "Choco Latte" beverage franchise. In this study try to see whether the franchise agreement "Choco Latte" including Franchise as stipulated in Government Regulation Number 42 of 2007 concerning Franchising and how the rights and obligations of the parties referred to in the franchise contract. The approach method used in this study is socio legal. Based on the results of this study, the rights and obligations of the parties referred to in the Choco Latte franchise contract as the franchisor give rights to the franchisee everything needed such as providing products, training services, network development and marketing and other rights stipulated in the agreement. While the franchisee's obligations to the franchisor include paying royalties, helping to develop the company in accordance with its vision and mission, carrying out business activities in accordance with the specified Standard Operating Procedures.Keywords: liability rights; franchise; trade secretsAbstrakAda banyak usaha waralaba, salah satu yang diteliti dalam penulisan ini yaitu franchise minuman “Choco Latte”. Dalam penelitian ini mencoba melihat apakah perjanjian waralaba “Choco Latte” termasuk Franchise sebagaimana diatur dalam Peraturan Pemerintah Nomor 42 Tahun 2007 Tentang Waralaba dan bagaimana hak dan kewajiban para pihak yang ditujukan dalam kontrak franchise. Metode pendekatan yang digunakan dalam penelitian ini adalah socio legal. Berdasarkan hasil penelitian ini, hak dan kewajiban para pihak yang ditujukan dalam kontrak franchise pihak Choco Latte sebagai franchisor memberikan haknya kepada franchisee segala sesuatu yang diperlukan seperti memberikan produk, pelayanan training, pengembangan jaringan maupun pemasaran dan hak-hak lain yang diatur dalam perjanjian. Sedangkan kewajiban franchisee terhadap franchisor diantaranya membayar royalti, membantu mengembangkan perusahaan sesuai dengan visi misinya, menjalankan kegiatan usaha sesuai dengan Standar Operasional Prosedur yang ditentukan.Kata kunci: hak kewajiban; franchise; rahasia dagang